If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-12x) + -3x = 0 Remove parenthesis around (-12x) -1 * -12x + -3x = 0 Multiply -1 * -12 12x + -3x = 0 Combine like terms: 12x + -3x = 9x 9x = 0 Solving 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '9'. x = 0 Simplifying x = 0
| 3x/10*6/1 | | -2+8x-6x=14 | | x-1/2=1(1/4) | | y=(y+8)(y+8)-2(y+8)-8 | | 1/2+x=2x+3/4 | | 12=-5k+32 | | (3v-1/3w)(v-1/5w) | | (X+3)/8=-6 | | 9(x-2)+6=-2 | | 2.15=x/740 | | 16x^2+150x-15=0 | | p-39=32 | | 8x-82=u | | -9-9=x | | 4+2/3x+9+1/3x | | 87=-2(-2-6x)-1 | | 16y^3-9=y-144y^2 | | X^2+2X+-4800=0 | | -9r-7-2r=26 | | 5*4/5+2=6 | | 2ax+2y=c | | 9t-18=0 | | -264=8(6a-3) | | -5n-2n+3=10 | | y=2y^2+6y+40 | | x+-14=-13 | | -5-4m=23 | | 3(-3)-[(-3)(-3)]=f | | 81=-3(5k-2) | | 4x-7(x+9)= | | (5v)(4)(6k)= | | 8x=36x+21 |